Tunable electrochemical approach for reduction of graphene oxide: Taguchi-assisted chemical and structural optimization - Moozarm Nia, P. (Electrochemical Society Inc., 2018)
The effect of significant parameters on the tuning of electrochemical reduction of graphene oxide (GO) and its electrochemical behavior toward ferri/ferrocyanide as a redox couple was investigated for the first time through a systematic methodical procedure. Reduced graphene oxide (rGOs) modified electrodes were prepared by electrodeposition on the surface of indium tin oxide (ITO) electrode under various GO concentrations, solution pH, scan rate and number of cycles. Taguchi is experimental design method involving orthogonal arrays, signal to-noise (S/N) ratio, analysis of variance (ANOVA) were employed to optimize reaction parameters and to analyze their effects on GO reduction. Cyclic voltammetry (CV) and Fourier-transform infrared spectroscopy (FTIR) analysis revealed that redox activity was least dependent on pH and GO concentrations whereas the use of higher scan rate and lower number of cycles led to more reduction of GO. On the other hand, the electrochemical behavior of samples deposited at higher scan rates totally improved despite the assumption that applying more potential causes more reduction of oxygen functional groups of graphene which are recognized to enhance the electron transfer. Moreover, electrochemical impedance spectroscopy (EIS) showed a lower charge transfer resistance for rGO which was prepared at higher scan rate. Such contrasting finding is precisely discussed in the manuscript to unveil the logical reasons. Â© 2018 The Electrochemical Society.